자연재난 피해자 경험에 대한 국내 질적 연구의 체계적 문헌고찰 - 이도은; Do-eun Lee; 박한송; Han-song Park; 김상호; Sang-ho Kim; 서주희; Joo-hee Seo (동의신경정신과학회지, 2021)
Objectives: To analyze the reports of qualitative research about natural disasters in Korea. Methods: Nine published qualitative research studies were selected for the analysis. The selected reports were analyzed by Consolidated Criteria for Reporting Qualitative Research (COREQ), a reporting guideline for qualitative research. In addition, each subject of the study was qualitatively synthesized. Results: In the quality assessment using COREQ, detailed information about the researchers were insufficient. The results of the studies were integrated into six themes: “Disaster experience”, “Disaster damage”, “Dealing with disasters”, “Disaster compensation issues”, “Arbitration Resources”, and “Post-disaster change”. Conclusions: In further qualitative research on natural disasters, it is necessary to report the research according to the COREQ checklist. Based on the results of this study, continuous attention and research are needed to explore the areas of Korean medicine care in the event of a disaster.